Study on intrinsic innervations and microvasculature of pancreas of albino rat - Ahmed, Rayaz; Ramayya, P. Jagapathi; Raju, N. K.B; Kumar, R .V. Suresh; Rao, S. Dhilleswara (Indian Journal of Veterinary Anatomy, 2018)
The pancreas of rat consisted of several nerve fibres both in the exocrine and the endocrine parts. The pancreatic nerve plexus were of four types viz., periacinar plexus, periinsular plexus, perivascular plexus and periductal plexus. Many neurons were observed as isolated cells and they aggregated to form small and large ganglia. The lymph vessels were present in the interlobular and intralobular connective tissue septa in the exocrine part of pancreas of rat. But, the endocrine portion was devoid of lymph vessels.